TATHBÎQ MANHAJ TA’LÎM AL-LUGHAH AL-‘ARABIYYAH ‘ALA ASÂS AL-TAHSHÎL AL-DIRÂSÎ FÎ AL-JÂMI’ÂT AL-ISLÂMIYYAH BI MATARAM INDONESIA - Nasarudin, Nasarudin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This study aimed to reveal the process of learning as an implementation of the Arabic language curriculum based on learning outcomes in two Arabic education study programs at Mataram State Islamic University and Muhammadiyah University Mataram. This research used a qualitative approach descriptive types with multi-site studies. The research findings unveiled that the process of implementation the Arabic language curriculum based on learning outcomes that refers to the Indonesian Qualification Framework (IQF) combined two approaches, namely student-centered learning (STL) and teacher-centered learning (TCL) by varying the use of learning methods in achieving learning outcomes set in the Semester Learning Plan. In addition, the lecturers apply the SCL approach more than the TCL.